2012
DOI: 10.7860/jcdr/2012/4218.2531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Persistant Median Artery

Abstract: Introduction: Neurovascular variations in the upper limb are common and they are well documented. An accurate knowledge of the normal and the variant anatomy of the median nerve and the median artery are important for clinical procedures and for vascular surgeries. The persistant median artery is one such anomaly which was seen in 6.6% (4) of the 60 upper limbs which were dissected in the present study, it being bilateral in one cadaver. Material and Methods:The present study was conducted on 60 upper limbs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
1
26
1
3
Order By: Relevance
“…This statement is consistent with our study results which revealed that the PMA in the carpal tunnel could occupy an anterior, anterolateral, or even an anteromedial position. The PMA could also occur alongside one of the most common variations of the median nerve, a bifid median nerve [35,36]. If the median nerve is bifid, the PMA could be located between the 2 nerve bundles, as observed in 2 cases in our study.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This statement is consistent with our study results which revealed that the PMA in the carpal tunnel could occupy an anterior, anterolateral, or even an anteromedial position. The PMA could also occur alongside one of the most common variations of the median nerve, a bifid median nerve [35,36]. If the median nerve is bifid, the PMA could be located between the 2 nerve bundles, as observed in 2 cases in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Coexistence of PMA and muscular variations has also been reported. Singla et al [36] described a case in which the PMA penetrated and divided the median nerve into 2 halves which joined to form a neural loop around the artery. Kachlik et al [34] found coincidence of superficial brachiomedian artery and bitendinous palmaris longus muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the most important studies of over 100 specimens (available to the authors) to see the incidence range. For other detailed data [ 9 , 10 ].…”
Section: The Variantsmentioning
confidence: 99%